2010
DOI: 10.1111/j.1466-8238.2010.00570.x
|View full text |Cite
|
Sign up to set email alerts
|

Recent vegetation changes at the high‐latitude tree line ecotone are controlled by geomorphological disturbance, productivity and diversity

Abstract: Aim We test how productivity, disturbance rate, plant functional composition and species richness gradients control changes in the composition of high-latitude vegetation during recent climatic warming.Location Northern Fennoscandia, Europe. MethodsWe resampled tree line ecotone vegetation sites sampled 26 years earlier.To quantify compositional changes, we used generalized linear models to test relationships between compositional changes and environmental gradients. ResultsCompositional changes in species abu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

11
127
2

Year Published

2012
2012
2019
2019

Publication Types

Select...
8

Relationship

4
4

Authors

Journals

citations
Cited by 133 publications
(144 citation statements)
references
References 82 publications
11
127
2
Order By: Relevance
“…In line with this hypothesis, an increased abundance of shrubs has been observed in geomorphological features where intense soil frost actions possibly hampered during the last decades due to recent warming Frost et al 2013). By exposing mineral soil, cryogenic disturbance processes can create gaps in the existing vegetation where seeds can germinate and species can establish (Sutton et al 2006;Virtanen et al 2010;Frost et al 2013). However, geomorphological disturbance can function as an ecological filter, hindering disturbance intolerant plants (e.g., trees) from taking advantage of a warmer climate (Macias-Fauria and Johnson 2013).…”
Section: Introductionmentioning
confidence: 50%
See 1 more Smart Citation
“…In line with this hypothesis, an increased abundance of shrubs has been observed in geomorphological features where intense soil frost actions possibly hampered during the last decades due to recent warming Frost et al 2013). By exposing mineral soil, cryogenic disturbance processes can create gaps in the existing vegetation where seeds can germinate and species can establish (Sutton et al 2006;Virtanen et al 2010;Frost et al 2013). However, geomorphological disturbance can function as an ecological filter, hindering disturbance intolerant plants (e.g., trees) from taking advantage of a warmer climate (Macias-Fauria and Johnson 2013).…”
Section: Introductionmentioning
confidence: 50%
“…The increased vegetation cover could in principal further reduce the differential heave, but we think that the vegetation cover and organic horizon depth, which has been observed to influence activity in non-sorted circles from the area (Klaus et al 2013), are still too sparse for this to be realised. Based on previous studies (Virtanen et al 2010;le Roux et al 2013; le Roux and Luoto 2014), we expected that cryogenic disturbance could also facilitate the establishment of species and cause vegetation changes. Specifically, circles have been shown to be favourable sites for seed germination (Sutton et al 2006;Frost et al 2013) and could thus facilitate the spread of species.…”
Section: Vegetation Changes In Non-sorted Circles During the Last Thrmentioning
confidence: 99%
“…Whereas the study of temperature limitation of physiological pathways in woody vegetation is fundamental, it is insufficient to explain the complex reality of landscape-scale (ecologically relevant) high-elevation tree cover, because it overlooks the fact that climatic limitation can prevail only on a small proportion of the landscape. Together with temperature, trees tend to experience other controlling mechanisms, such as those related to the physical characteristics of the lithosphere on which they grow (14)(15)(16)(17). Although some of our model variables are linked to avalanches or landmass movements, the present study did not directly address disturbance processes [e.g., wildfires, insect outbreaks (23)], which would add even more complexity to the dynamics of subalpine tree-cover change under warmer climate scenarios.…”
Section: Discussionmentioning
confidence: 99%
“…Changes in high-elevation tree cover will, thus, result from modifications on any of these controlling processes. Although topography and geomorphology have been identified as important in setting the observed heterogeneity of highelevation mountain tree cover (13)(14)(15)(16)(17)(18)(19), the effect of geomorphology on present and future high-elevation tree cover remains unquantified, and site-based studies overwhelmingly treat terrain physiognomy as a uniform neutral background. To address these questions, we conducted a statistical modeling exercise of tree presence at high spatial resolution (10 m) over a ∼100-km 2 area comprising the geologic and geomorphic diversity found in the Front Ranges of the Canadian Rocky Mountains of Alberta ( Fig.…”
mentioning
confidence: 99%
“…Some studies on relatively species-poor communities in the Arctic also found little change in species richness (Prach et al 2010;Callaghan et al 2011b;Daniëls and de Molenaar 2011). Virtanen et al (2010) report a more complex pattern with an increase of species in species-poor communities, while species richness remains ''relatively constant'' in species-rich communities. In contrast, we did not see any correlation between change in species number and either initial species richness or present species richness.…”
Section: Discussionmentioning
confidence: 99%